GUIDANCE ON THE USE OF SIMPLE FINANCIAL RATIOS TO MEASURE MSME PERFORMANCE - Aloisius Hama; Herlambang Pudjo Santoso (Pedagogic Research-Applied Literacy Journal, 2024)
MSMEs play a strategic role in the national economy. They continue to face limitations in managing and evaluating business financial performance. Low levels of financial literacy cause MSME actors to experience difficulties in objectively assessing business profitability. This community service activity aims to improve MSME actors’ understanding of financial performance measurement through the use of simple financial ratios, particularly the Net Profit Margin. The implementation method employed a participatory approach through technical guidance, interactive discussions, and case study simulations. The results of the activity indicate an improvement in participants’ understanding of the concept of net profit and their ability to calculate and interpret the ratio. Satisfaction survey results show that more than 90% of participants expressed satisfaction to high satisfaction with the materials, methods, and benefits of the activity. Overall, this activity was effective in improving MSME financial literacy, has the potential to encourage more rational and sustainable business decision-making.